Pengaruh Kualitas Pelayanan dan Kepuasan Konsumen terhadap Loyalitas Konsumen PT.Wahana Prestasi Logistik Cabang Bogor Ciriung Mayor Oking - Annisa Pratiwi Utami; Ratnawaty Marginingsih (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Customer loyalty is the mst important key in a company, because it can increase profits and determine the survival of a company. Loyalty can be formed by good quality service and customer satisfaction resulting from the services provided by the company. The purpose of this research is to determine the influence of service quality and customer satisfaction on customer loyalty at PT. Wahana Logistics Achievement Bogor Branch Ciriung Mayor Oking. This research uses quantitative methods with SPSS Version 25 software. The samples used for data collection were customer of PT.Wahana Achievement Logistics consisted of 60 respondents with sampling using random sampling. The coefficient of determination test results (R2) use an adjusted R-square value of 0,677, wich means that 67,7% of service quality (X1) and costomer satisfaction (X2) have an influence on costomer loyalty, and the remaining 32,3% is influenced by variables not researched by the author. The results of the f test simultaneously show that the variables of service quality and customer satisfaction and positive effect with a sig value of 0,000 < 0,05 and Fcount of 62,722 > 4,007 Ftable on the costomer loyalty variable. From the calculation of the results of the multiple linear regression test, it shows that costomer loyalty is influenced by the service quality variable equal to b1 = 0,620 and the costomer satisfaction variable b2 = 0,301